Large seasonal and interannual variations of biogenic sulfur compounds in the Arctic atmosphere (Svalbard; 78.9° N, 11.9° E) - Jang, Sehyun; Park, Ki-Tae; Lee, Kitack; Yoon, Young Jun; Kim, Kitae; Chung, Hyun Young; Becagli, Silvia; Lee, Bang Yong; Traversi, Rita; Eleftheriadis, Konstantinos; Krejci, Radovan; Hermansen, Ove (2021)
Seasonal to interannual variations in the concentrations of sulfur aerosols (< 2.5 micron in diameter; non sea-salt sulfate: NSS-SO 4 2− anthropogenic sulfate: Anth-SO 4 2− biogenic sulfate: Bio-SO 4 2− methanesulfonic acid: MSA) in the Arctic atmosphere were investigated using measurements of the chemical composition of aerosols collected at Ny-Ålesund, Svalbard (78.9° N, 11.9° E) from 2015 to 2019. In all measurement years the concentration of NSS-SO 4 2− was highest during the pre-bloom period and rapidly decreased towards summer. During the pre-bloom period we found a strong correlation between NSS-SO 4 2− and Anth-SO 4 2− because more than 50 % of the NSS-SO 4 2− measured during the pre-bloom period was Anth-SO 4 2− , which originated in the northern Europe and was subsequently transported to the Arctic through the Arctic haze. Unexpected increases in the concentration of Bio-SO 4 2− aerosols (an oxidation product of dimethylsulfide: DMS) were occasionally found during the pre-bloom period and were obviously not produced in ocean areas in the proximity of Ny-Ålesund, but probably originated in distant regions to the south (i.e., the North Atlantic Ocean and the Norwegian Sea). The concentration of MSA (another oxidation product of DMS) during the pre-bloom period contrarily remained low, which was largely because of the greater loss of MSA relative to Bio-SO 4 2− and the suppression of condensation of gaseous MSA onto existing particles during the northward transport of air masses containing these components from distant ocean source regions. Moreover, the low light intensity during the pre-bloom period resulted in a low concentration of photochemically activated oxidant species including OH radicals and BrO and thus more favoured the oxidation pathway of DMS to Bio-SO 4 2− rather than to MSA, which acted to lower the MSA concentration at Ny-Ålesund. The concentration of MSA peaked in May or June, and was positively correlated with ocean biomass in the Greenland and Barents seas around Svalbard. As a result, the mean ratio of MSA to the DMS-derived aerosols was low (0.09 ± 0.07) for the pre-bloom period but high (0.32 ± 0.15) for the bloom and post-bloom periods. Our results indicate that the contribution of MSA to the growth of the newly formed particles to a size at which they could act as condensation nuclei was considerably greater during the bloom and post-bloom periods than during the pre-bloom period.